Scanning laser thermographic system for non-destructive evaluation of incipient thermal damages in aircraft composite panel - Musa, Afiqah (2018)
Composite materials applied in aerospace structure are getting popular due to advantages such as high specific strength and stiffness with favorable strength to weight ratio. However, incipient thermal damage (ITD) that can cause reduction of 60% of composite mechanical strength are still unable to be detected using conventional NDT&E method. This project aims to develop an effective NDT&E tool that can detect or evaluate ITD through these three objectives. First, to synchronize laser system, laser scanner system and thermal imager as an active infrared imaging system. Second, to develop corresponding data acquisition and noise removal algorithm for extraction of local temperature-time profiles. Third, to validate the effectiveness of the system and algorithm for non-destructive evaluation of ITD in glass fiber reinforced composite plate (GFRP). In correspondence to research objective, laser pulse was implemented as a powerful thermal energy source in thermography method for evaluating ITD. GFRP plate was insulted with high temperature at range of material glass transition temperature, 0.8T g,1.0 T g,1.1 T g,1.2 T g and 1.3 T g (T = 97°C,121°C,133°C,145°C and 157°C) at time t = 120, 60, 30, 15, 10 and 5 minutes to prepare ITD as well as thermal damage (TD) for reference. Focus was done on ITD which are insulted at borderline temperature of T g with relatively longer insult time; 0.8T g and 1.0 T g at t = 120,60,30 minute. ITD evaluation in this study are realized in the form of percentage difference between damage and reference derived from thermal contrast base principle. Following this, result gained represents outliers with respective to reference area and thus indicate detection of damage. Result gained for ITD at 0.8 T g are 1.93851%, 0.30561% and 0.20913% meanwhile 2.02966%, 1.73518% and 0.53167% at 1.0T g for t = 120,60,30 minute. A gradual decrement trend can be seen from longer insult time to lower insult time to indicate level of severity on damage detected. According to system resolution and capability, these values are within the range and thus proves the detection of ITD. Further verification done using ultrasonic method also proves the inability of conventional NDT&E method to detect ITD as expected. Hence, with proposed Scanning Laser Thermographic system, all ITD that were insulted with temperature at borderline of T g at relatively longer insult time had been successfully detected at minimum of 0.20913% at insult temperature; 0.8 T g with insult time t = 30 minute and at maximum of 2.02966% at insult temperature; 1.0 T g with insult time t = 120 minute.